2003
DOI: 10.1074/jbc.m212033200
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Stimulates p38-dependent Induction of Antiviral Genes in Neutrophils Independently of Paracrine Factors

Abstract: Lipopolysaccharide (LPS) induces neutrophils to synthesize and secrete pro-inflammatory cytokines and chemokines, which are regulated at both the transcriptional and translational level. We reported previously that neutrophils stimulated with LPS induce expression of genes typically expressed in response to stimulation with antiviral type I interferons (IFN), such as myxovirus resistance-1 (MX1). However, we present evidence that this response of neutrophils to lipopolysaccharide occurs in the absence of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 80 publications
2
27
2
Order By: Relevance
“…It is noteworthy that the induction of IFIT1 and IP-10, but not of TNF-␣ or IFN-␤, seems to require de novo protein synthesis. This fact, along with the LBP-dependent Tyk2 and STAT1 phosphorylation, is consistent with previous reports that the induction of these molecules is regulated by IFN-␤ (6,7,44).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It is noteworthy that the induction of IFIT1 and IP-10, but not of TNF-␣ or IFN-␤, seems to require de novo protein synthesis. This fact, along with the LBP-dependent Tyk2 and STAT1 phosphorylation, is consistent with previous reports that the induction of these molecules is regulated by IFN-␤ (6,7,44).…”
Section: Discussionsupporting
confidence: 80%
“…LPS also induces large amounts of antiviral proteins (6,7) and CXCR3 chemokines (8), all of which are known to be regulated by type I or II IFNs (9). Transcriptional regulation of these cytokines and chemokines is mediated by NF-B and IFN-regulatory factor (IRF)-3 (7).…”
mentioning
confidence: 99%
“…The reliability of our microarray neutrophil data is further illustrated by the fact that we observed no induction of either IL-6 or CCL2 signals in response to LPS, which have been shown to reflect the contamination of neutrophil RNA samples by RNA from monocytes and/or eosinophils (8,42). This possibly explains some discrepancies between the data reported herein and recent microarray data obtained from LPS-treated human neutrophils, which featured a dramatic up-regulation not only of IL-6 or CCL2 but also of many classically IFN␤-inducible mRNAs such as MX1, G1P2/ISG15, IFIT1, IFIT2, IFIT3, IFIT5, IFI35, and EIF2AK2/ PKR (69,70). In keeping with this interpretation, these earlier microarray studies used neutrophil preparations that were stated to contain a substantial proportion of contaminant cells (as high as 5%) (69,70) that may well give rise to false positives.…”
Section: Discussioncontrasting
confidence: 56%
“…This possibly explains some discrepancies between the data reported herein and recent microarray data obtained from LPS-treated human neutrophils, which featured a dramatic up-regulation not only of IL-6 or CCL2 but also of many classically IFN␤-inducible mRNAs such as MX1, G1P2/ISG15, IFIT1, IFIT2, IFIT3, IFIT5, IFI35, and EIF2AK2/ PKR (69,70). In keeping with this interpretation, these earlier microarray studies used neutrophil preparations that were stated to contain a substantial proportion of contaminant cells (as high as 5%) (69,70) that may well give rise to false positives. Clearly, the purity of the cell populations will increasingly constitute an important concern in future microarray studies conducted in primary cells.…”
Section: Discussioncontrasting
confidence: 56%
“…Change in ISG expression and increasing sCD14 with viremia may evidence increasing microbial translocation, as microbial products were associated with interferon alpha activation in HIV-1 viremic patients (17) and may contribute to the shift in monocyte ISG expression and apoptosis induction (64,65). Previous studies have demonstrated elevated sCD14 in multiple comparisons of HIV ϩ to HIV Ϫ donors (14,16,17,(66)(67)(68), and while we demonstrated an association with viral load and CD4 count ( Fig.…”
Section: Cd16mentioning
confidence: 53%